Partisanship and local fiscal policy: Evidence from Brazilian cities - Raphael Rocha Gouvêa; Daniele Girardi (University of Massachusetts, Department of Economics, 2019)
We study the role of political parties in shaping local fiscal policy in the context of Brazilian cities in the 2004-2016 period. Using a regression-discontinuity design, we find no effect of left-wing mayors on the size of the city government nor on the allocation of spending across main budget categories (current spending, investment and personnel). We do find a modest, significant and robust positive effect on the share of social expenditures. The (close) election of a left-wing mayor tends to raise the share of social expenditures by around 0.6 percentage points in our preferred RD specification. We then explore possible mechanisms which could bring about substantial fiscal policy convergence between political parties in Brazilian cities. We exploit oilrelated revenue windfalls to explore the role of institutional constraints, and build an index of Tiebout competition to measure the role of the latter. We find support for the institutional constraints hypothesis in explaining the limited extent of spending allocation effects, and little support for the Tiebout-competition hypothesis.
Keywords: 330